Comparison of 18F-FDG PET/CT Criteria for the Prediction of Therapy Response and Clinical Outcome in Patients With Metastatic Melanoma Treated With Ipilimumab and PD-1 Inhibitors. (March 2020) - Annovazzi, Alessio; Vari, Sabrina; Giannarelli, Diana; Pasqualoni, Rosella; Sciuto, Rosa; Carpano, Silvia; Cognetti, Francesco; Ferraresi, Virginia
Abstract : N/A: Immunotherapy currently represents one of the most effective therapies in metastatic melanoma. However, its indirect antineoplastic activity through the immune system has raised relevant challenges for diagnostic imaging in the evaluation of the response to treatment. Purpose: The aim of this retrospective study was to compare the diagnostic accuracy of different 18 F-FDG PET/CT criteria to predict therapy response and clinical outcome in melanoma patients treated with immune checkpoint inhibitors. Patients and Methods: Fifty-seven patients with metastatic melanoma treated with ipilimumab (n = 25; group 1) or with PD-1 inhibitors (n = 32; group 2) who performed an 18 F-FDG PET/CT scan before treatment (PET0) and 12 to 18 weeks later (PET1) were retrospectively evaluated. Response at PET1 was evaluated according to RECIST 1.1, EORTC, PERCIMT (PET Response Evaluation Criteria for Immunotherapy), and by percentage change of metabolic tumor volume (MTV) and total lesion glycolysis of up to 5 target lesions. Performance of each criterion at PET1 to predict clinical benefit at 6 months since starting immunotherapy was assessed and correlated to progression-free survival. Results: In group 1, the best predictor of therapy response was MTV combined with PERCIMT criteria (accuracy, 0.96). In group 2, overlapping results were found for EORTC, MTV, and total lesion glycolysis (accuracy, 0.97). The reliability of the above parameters was also confirmed in the progression-free survival analysis. Conclusions: 18 F-FDG PET/CT performed after 3 to 4 months since starting immunotherapy can correctly evaluate response to treatment and can also able to predict long-term clinical outcome. Performance of 18 F-FDG PET/CT and criteria for response assessment is influenced by the class of treatment.